KESIAPAN JALUR DAN LOKASI EVAKUASI PUBLIK MENGHADAPI RESIKO BENCANA GEMPA DAN TSUNAMI DI KOTA PADANG (Studi Manajemen Bencana) - Alhadi, Zikri (Humanus, 2014)
This article discusses about the preparedness of the evacuation lanes and sites for Padang citizens in facing earthquake and tsunami. In disaster management, the proper evacuation lanes and sites to be used for self-rescue plan is crucial to be fulfilled by stakeholders. In Padang city, some evacuation lanes and sites have not met the needs of the number of people predicted to evacuate when the disaster comes. This can be seen when several potential-tsunami-triggered quakes struck Padang, the citizens’ evacuation process, vertically or horizontally, were significantly challenged. The speed of reaching the evacuation site is important in saving many lives when tsunami really happens in Padang.Key words: disaster management, evacuation, earthquake and tsunami